New fusion and selection approaches for estimating the remaining useful life using Gaussian process regression and induced ordered weighted averaging operators - Bouzenita, Mohammed; Leila-Hayet Mouss; Melgani, Farid; Toufik Bentrcia (Quality and Reliability Engenieering International Journal (QREIJ), 2020)
In this paper, we propose new fusion and selection approaches to accurately predict the remaining useful life. The fusion scheme is built upon the combination of outcomes delivered by an ensemble of Gaussian process regression models. Each regressor is characterized by its own covariance function and initial hyperparameters. In this context, we adopt the induced ordered weighted averaging as a fusion tool to achieve such combination. Two additional fusion techniques based on the simple averaging and the ordered weighted averaging operators besides a selection approach are implemented. The differences between adjacent elements of the raw data are used for training instead of the original values. Experimental results conducted on lithium-ion battery data report a significant improvement in the obtained results. This work may provide some insights regarding the development of efficient intelligent fusion alternatives for further prognostic advances.